(untitled) (Pakistan Journal of Kidney Diseases, 2021)
Patients requiring immunosuppressive therapy after transplantation are susceptible to infection by a variety of common and uncommon pathogens, and infection has been the major cause of death in organ transplant recipients. Here we present one of a kind case where klebsiella pneumonia led to a fatal and life threatening complication i.e. gastro pulmonary fistula in a renal transplant recipient.